DEVELOPING A STUDENT SELF-DISCLOSURE MEASURE: A PILOT STUDY - Jebbour, Mohsine (Yayasan Visi Intan Permata, 2020)
This pilot study was designed to introduce a student self-disclosure measure with 183 participants enrolled in the English department at a Moroccan university. The types of self-disclosures inherent in language learning theory guided the development of a ten-item questionnaire. The instrument measured the participants? self-report of frequent self-disclosures with reference to the class they were attending. Upon collection of data, the questionnaire was subjected to exploratory factor analysis. The findings of the unrotation analysis showed that the student self-disclosure measure is unidimensional, as nine items loaded highest on the first factor and had an acceptable internal consistency. However, results from the rotation analysis revealed that the student self-disclosure measure consists of two dimensions, which were labelled as frequent types of self-disclosure and infrequent types of self-disclosure based on their mean scores. Although the seven items tapping frequent types of self-disclosure may be used to create a unidimensional measure, especially that the construct reached an acceptable internal reliability, there is room for ensuring a sound collection of data and analysis to improve the quality of the questionnaire in the main study.